2006
DOI: 10.1109/tbme.2005.862570
|View full text |Cite
|
Sign up to set email alerts
|

Method of Propulsion of a Ferromagnetic Core in the Cardiovascular System Through Magnetic Gradients Generated by an MRI System

Abstract: Abstract-This paper reports the use of a magnetic resonance imaging (MRI) system to propel a ferromagnetic core. The concept was studied for future development of microdevices designed to perform minimally invasive interventions in remote sites accessible through the human cardiovascular system. A mathematical model is described taking into account various parameters such as the size of blood vessels, the velocities and viscous properties of blood, the magnetic properties of the materials, the characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(133 citation statements)
references
References 23 publications
1
132
0
Order By: Relevance
“…Several previous works also used a clinical MRI system to guide and position ferromagnetic beads [75,76]. Mathieu at al.…”
Section: Actuation With Magnetic Field Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous works also used a clinical MRI system to guide and position ferromagnetic beads [75,76]. Mathieu at al.…”
Section: Actuation With Magnetic Field Gradientmentioning
confidence: 99%
“…Mathieu at al. [75] presented how to use a clinical MRI system to propel micro devices for the first time. The proposed mathematical model and the results of experiments show that a MRI system could provide enough magnetic force to move a ferromagnetic bead inside human cardiovascular system.…”
Section: Actuation With Magnetic Field Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also significant potential advantages to seismic actuation, particularly in medical applications. Magnetic microrobots are already effectively leveraging existing magnetic imaging systems for control and visualization [9]. Scaled appropriately, vibrational actuation might be adapted to use existing ultrasonic imaging systems, which are more affordable and less hazardous than magnetic imaging systems.…”
Section: Open Accessmentioning
confidence: 99%
“…[8,9] Other magnetic microrobots may be directly manipulated by an external magnetic field gradient. [10,11] Mathieu et al [10] used a magnetic resonance imaging (MRI) system to actuate magnetized particles and demonstrated that millimeter-sized ferromagnetic spheres can be propelled inside larger-diameter sections of arterial systems by using a field gradient of a few tens of mT=m, which is within the range of MRI systems. However, for smaller microrobots, larger magnetic NOMENCLATURE B magnetic flux density…”
Section: Introductionmentioning
confidence: 99%